Sufficient Condition for Partial Optimality for (max, +)-Labeling Problems and its Usage - Kovtun, I. (Управляющие системы и машины, 2011)
Для (max,+)-задач разметки сформулированы достаточные условия оптимальности метки в каждом пикселе изображения. Описан алгоритм, позволяющий определить оптимальные метки в некоторых пикселах и тем самым существенно снизить сложность исходной задачи. Sufficient conditions for the optimal label detection in every pixel are formulate. An algorithm is described which makes it possible to define the optimal labels in some pixels and to decrease essentially the complexity of the original problem. Для (max, +)-задач розмітки сформульовано достатні умови оптимальності мітки у кожному пікселі зображення. Описано алгоритм, що дозволяє визначити оптимальні мітки у деяких пікселах, завдяки чому суттєво зменшується складність вихідної задачі.